Integrated design of large and medium‐sized low profile frequency reconfigurable antenna array. Issue 6 (24th March 2021) - Deng, Xiaoqiao; Li, Yuanjiang; Ding, Zhenfeng; Tian, Yubo; Bao, Lin; Li, Xiaolong
Abstract: In this paper, in order to solve the limitations of conventional technology schemes, a new scheme for large and medium‐sized frequency reconfigurable antenna array (FRAA) with low profile is proposed by combining advanced technologies such as new electromagnetic materials, reconfigurable antenna and integrated design. The proposed FRAA operating in X and Ku bands consists of a 4 × 4 antenna array, a w ide‐band feed network, a dual‐band electromagnetic band gap (EBG) plate and integrated bias network. The distance between antenna array and reflective plate has been reduced by 80.0% by applying an EBG structure. The influence of bias network on antenna performance is effectively reduced, and the performance of X/Ku two‐band antenna is ensured through the integrated optimization design of the bias network, EBG reflector plate and antenna array. Both simulation and test results show that the proposed FRAA has good performance.